2022
DOI: 10.1161/circep.122.010992
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Pulsed Field Ablation With Biphasic Waveforms in an In Vivo Heart Model: The Role of Frequency

Abstract: Background: Pulsed field ablation (PFA) is a novel nonthermal cardiac ablation technology based on irreversible electroporation. Unfortunately, the characteristics of the electric field waveforms used in clinical and experimental PFA are not typically reported. This study examines the effect of the frequency of biphasic waveforms and compares biphasic to monophasic waveforms. Methods: A total of 29 Sprague-Dawley rats were treated with PFA using an epic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…This is consistent with previous in vivo and in vitro reports, including recent studies utilizing hiPSC-CMs. 13,14,33,34,37,41 In regions of the culture subjected to lower field intensities, a delayed recovery of electric activity could be detected. These findings further emphasize that initial electric silencing following PFA does not necessarily translate into durable lesions, and that recovery of electric activity may occur over the course of hours/days.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous in vivo and in vitro reports, including recent studies utilizing hiPSC-CMs. 13,14,33,34,37,41 In regions of the culture subjected to lower field intensities, a delayed recovery of electric activity could be detected. These findings further emphasize that initial electric silencing following PFA does not necessarily translate into durable lesions, and that recovery of electric activity may occur over the course of hours/days.…”
Section: Discussionmentioning
confidence: 99%
“…Tomás et al [ 32 ] applied PFA on the epicardium of a rat, and the record of the optical temperature probe located at the point of contact between the electrode and the tissue showed that the temperature sharply increased during each pulse and subsequently slowly dissipated by conduction between consecutive pulses. The characteristics of the maximum temperature curve of myocardium during PFA in this study are consistent with the above.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the size of the myocardial ablation volume is in cubic mm, and the difference in the size of the myocardial ablation volume between the CHT method and CFD method is insignificant for values less than 1 mm 3 since this value is approximate to the deviation (±0.5 mm) observed in experimental studies [ 5 ]. Likewise, the differences in the maximum temperature of myocardium and blood between the CHT method and CFD method are considered insignificant for values less than 1 °C since this value is the system security (±0.5 °C) of the temperature fiber optic sensor used to measure the temperature rise during PFA [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…From a clinical perspective, the level of muscle contractions observed would require the use of general anesthesia and neuromuscular blockade. As previously shown, 11 waveform could be optimized to reduce muscle contractions.…”
Section: Limitationsmentioning
confidence: 94%
“…The waveform used was validated in a previous study in small animals. 11 Namely, it consisted in a sequence 10 biphasic bursts with 100 μs duration for each burst. The bursts were delivered with a 1 second delay between them (ie, 10 seconds total treatment duration per point).…”
Section: Methodsmentioning
confidence: 99%